Intersecting Roadmaps: Resolving Tension Between Profession-Specific and University-Wide Graduate Attributes - ElAtia, Samira; Carey, Jason P.; Jamieson, Marnie; Alibrahim, Bashair; Ivey, Marcus (Canadian Journal of Higher Education, 2021)
Can we map university-wide graduate attributes to specific program requirements? Can we develop and manage an integrated assessment process? In this article, we present a seven-month long project where we attempted to map generic university graduate attributes (UGAs) to required engineering program graduate attributes in a large Canadian research institution. The purpose of the project was to explore the intersection of the UGAs with engineering graduate attributes, evaluate the accreditation process, develop a mapping process, and examine management strategies for assessing both sets of graduate attributes, all the while keeping the continual improvement process attractive to students, instructors, and administrators. Using a modified dialectical inquiry, two groups worked on the mapping process: one from engineering, the other from social sciences (Education and Arts), to ensure objectivity of comparison. Both forward and backward mapping took place. Results demonstrated that, although generic, UGAs may not necessarily capture specific professional program graduate attributes. The study also highlighted the need for more revisions and updates of UGAs by including various stakeholders who can substantially contribute to the implementation and assessment of UGAs.